The Challenge of Rock Mass Classification of Anisotropic Rockmasses - Saroglou, Charalampos (Rock mechanics and rock engineering, 2025)
Rock mass classification of anisotropic rockmasses has always been a challenge for the Rock Engineering industry. The widely used rock mass classification systems, such as RMR, Q and GSI have been tested in practice over the years and in many cases, it proved that they could provide a classification of such rockmasses only if reasonable modifications to their original form were pursued. The intention of the paper is to review the state of the art of rock mass classification systems for anisotropic rockmasses. The primary challenge is the fact that in anisotropic rockmasses, classifications are only applicable when the failure is not governed by the orientation and the properties of the anisotropic planes. In cases where failure is not controlled by the anisotropy planes, it is critical to classify the rockmass appropriately considering the complexity due to anisotropy. A review of the available tools for the classification of such rockmasses is presented. Recently, anisotropic rock mass rating (ARMR) system provided a means for quantitative rock mass classification for anisotropic rockmasses. The paper presents a review from the application of the system in various cases studies, mainly from rock slope engineering and tunneling projects and provides a comparison with RMR and GSI. The method of application of ARMR is also discussed. The paper gives further insight for future challenges and developments of rockmass classifications for anisotropic rockmasses.